2023
DOI: 10.1002/pan3.10523
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating human–nature connectedness in three EU countries: A pro‐environmental behaviour perspective

Abstract: Strengthening positive human–nature relationships is seen as a way to more pro‐environmental behaviour and leads to a greater environmental sustainability. Therefore, understanding human–nature relationships has attracted increasing attention among researchers. Nature connectedness is a concept developed to measure such relationships. Since nature connectedness is complex and context dependent phenomenon, more research comparing sociocultural and environmental factors within societies in different countries is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 105 publications
(166 reference statements)
0
1
0
Order By: Relevance
“…According to a study by Mikusiński et al (2023), value orientations are one of the most important factors associated with human-nature connectedness (related to pro-environmental attitudes; Klaniecki et al, 2018). However, a study by De Groot and Steg (2007) showed that value orientations were strongly related to personal norms and awareness of consequences only in the case of Sweden (and not in the case of four other investigated countries: the Netherlands, Italy, Austria, and the Czech Republic).…”
Section: Pro-environmental Behaviors In Poland and Swedenmentioning
confidence: 99%
“…According to a study by Mikusiński et al (2023), value orientations are one of the most important factors associated with human-nature connectedness (related to pro-environmental attitudes; Klaniecki et al, 2018). However, a study by De Groot and Steg (2007) showed that value orientations were strongly related to personal norms and awareness of consequences only in the case of Sweden (and not in the case of four other investigated countries: the Netherlands, Italy, Austria, and the Czech Republic).…”
Section: Pro-environmental Behaviors In Poland and Swedenmentioning
confidence: 99%